2014
DOI: 10.3389/fgene.2014.00099
|View full text |Cite
|
Sign up to set email alerts
|

miR-191: an emerging player in disease biology

Abstract: Specific microRNAs have emerged as key players in disease biology by playing crucial role in disease development and progression. This review draws attention to one such microRNA, miR-191 that has been recently reported to be abnormally expressed in several cancers (>20) and various other diseases like diabetes-type 2, Crohn’ s, pulmonary hypertension, and Alzheimer’ s. It regulates important cellular processes such as cell proliferation, differentiation, apoptosis, and migration by targeting important transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 82 publications
3
118
0
2
Order By: Relevance
“…This confirms that ASC and MSC EVs have both pro-angiogenic properties [11,24] and are able to restore tube formation ability in endothelial cells damaged by high glucose conditioning. These biological effects are consistent with previous observation that MSC EVs and ASC EVs contain several proangiogenic factors [11][12][13][14][24][25][26][27] and miRNAs [20][21][22]46]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This confirms that ASC and MSC EVs have both pro-angiogenic properties [11,24] and are able to restore tube formation ability in endothelial cells damaged by high glucose conditioning. These biological effects are consistent with previous observation that MSC EVs and ASC EVs contain several proangiogenic factors [11][12][13][14][24][25][26][27] and miRNAs [20][21][22]46]. …”
Section: Resultssupporting
confidence: 93%
“…Recent studies showed that EVs derived from MSC (MSC EVs) contain vascular endothelial growth factor (VEGF), transforming growth factor β1 (TGFβ1), interleukin 8 (IL-8) [12,13], hepatocyte growth factor (HGF) [14][15][16], HES Family BHLH transcription factor 1 (HES1) [17], and human T-cell factor 4 (TCF4) [18,19], but also miRNA stimulating angiogenesis, such as miR210, miR-126, miR-132, miR-21 [20], miR-222, let-7f [21,22], and cell-cycle progression and proliferation, such as miR-191, miR-222, miR-21, let-7a [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…miR-191 is a stress-sensitive miRNA that has been extensively studied in cancer pathologies and reduced levels of this miRNA are shown in connection with diabetes mellitus. 16,23 Modulation in miR-191 expression regulates apoptosis, cell proliferation, migration, and cell cycle under various pathological settings. 23 Interestingly, altered plasma levels of endothelial-rich miRNAs, for example, miR-191 or miR-126 is reported to reflect underlying endothelial dysfunction in diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…16,23 Modulation in miR-191 expression regulates apoptosis, cell proliferation, migration, and cell cycle under various pathological settings. 23 Interestingly, altered plasma levels of endothelial-rich miRNAs, for example, miR-191 or miR-126 is reported to reflect underlying endothelial dysfunction in diabetes mellitus. 16 miR-191 is coexpressed with the miR-191/425 cluster which is highly conserved in higher eukaryotes 24 and our plasma miRNA profiles also confirm a unidirectional changes in circulating plasma levels of both clustered miRNAs from patients with diabetes mellitus with impaired wound healing compared with diabetics with no chronic wound.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of miRs negatively regulate the expression of their target genes by binding to the 3'-untranslated regions (3'-UTRs) of mRNA, leading to mRNA degradation or translational suppression (11,12). In numerous biological processes, including cell proliferation, differentiation, migration and apoptosis, miRs are involved in regulating the expression of multiple target genes (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%